2017
DOI: 10.1049/oap-cired.2017.0148
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of voltage quality parameters in MV distribution grid

Abstract: This paper describes the impact of operation of big customers on voltage quality parameters in medium voltage distribution grids. The survey is based on the evaluation of 45 voltage quality measurements which were carried out in 15 different delivery points of other customers. These 45 measurements were made in years 2014, 2015 and 2016 (15 measurements a year) and were evaluated according to standard EN 50160. The impact on voltage variations and other voltage quality parameters was analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…The limit set by the standard [14] for the k u factor is 2 %. In [10], all the measured k u values are in the range between 0.1 % and 0.7 %. In [15], PQ is monitored in substations and distribution feeders at various voltage levels (from 13.8 kV to 138 kV).…”
Section: A Measurement Of Pq Phenomenamentioning
confidence: 95%
See 3 more Smart Citations
“…The limit set by the standard [14] for the k u factor is 2 %. In [10], all the measured k u values are in the range between 0.1 % and 0.7 %. In [15], PQ is monitored in substations and distribution feeders at various voltage levels (from 13.8 kV to 138 kV).…”
Section: A Measurement Of Pq Phenomenamentioning
confidence: 95%
“…It has been found that the P lt index quite often exceeds the limit set by standard [17] and the maximum observed value is 1.7. In [10], the maximum observed P lt is 2.5 and the corresponding P st is equal to 3. In [11], P lt ranges from 1.35 to 3.53.…”
Section: A Measurement Of Pq Phenomenamentioning
confidence: 95%
See 2 more Smart Citations
“…Based on previous reports [21,22], the total harmonic distortion was measured at 30 different grids in the Czech Republic at different intervals. The measurements and evaluation of the harmonic level were made by the E.ON Distribution in the Czech Republic, operated by the company E.ON Czech Republic.…”
Section: Distance Relay: Tripping Time Vs Thd Levelmentioning
confidence: 99%